Living the Vita: Performative Education Through Collaborative Autoethnographic Megapuppetry - Collins, Kevin D.; Collins, Cynthia E. (Cindy) (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes, 2024)
In this article, Cindy and I explore our creative megapuppetry activism. As avocational advocates of social change in the state of Tennessee, we describe our lived experiences of educating adults about social issues in public spaces through protests, rallies, and parades. We use this description as a phenomenological autoethnography, investigating these experiences through ideation, creation, and realization. Because these creative educational efforts have been central to our lives, we place our practice in the rubric of Arendt’s (1958) vita contemplativa/vita activa, arguing that the practices aspire to a fulfilled life, satisfying the dictates of The Human Condition (Arendt, 1958).